2004
DOI: 10.1507/endocrj.51.415
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Regulation of the Thyroids: Negative Regulation on Thyroid Hormone Levels in Euthyroid Subjects and Inhibitory Effects on Iodide Uptake and Na+/I- Symporter mRNA Expression in Rat FRTL-5 Cells

Abstract: Abstract. Leptin receptors are distributed throughout the body and leptin has been shown to have various effects. As we have recently demonstrated a positive correlation between serum leptin levels and TSH in euthyroid subjects, we investigated the effect of leptin on the thyroids. It was observed that serum leptin levels were negatively correlated with free thyroxine/TSH ratios in the serum of euthyroid female subjects. This suggests that leptin may modulate TSH effects. RT-PCR for leptin receptor expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…These observations indicate a direct stimulatory effect of leptin on the thyroid gland or on the peripheral metabolism of T 4 and T 3 in humans with reduced body weight. On the other hand, recent studies have shown direct inhibitory effects of leptin on the ability of thyrocytes to take up iodide in rat thyroid cells (27,37).The transport of iodide is a fundamental step in thyroid hormone biosynthesis and is catalyzed by the Na ϩ -I Ϫ symporter (NIS), an intrinsic membrane protein localized at the basolateral membrane of thyrocytes (20). Leptin directly inhibits iodide uptake induced by TSH in FRTL-5 cells (27) and in thyroids from fed adult rats (37).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…These observations indicate a direct stimulatory effect of leptin on the thyroid gland or on the peripheral metabolism of T 4 and T 3 in humans with reduced body weight. On the other hand, recent studies have shown direct inhibitory effects of leptin on the ability of thyrocytes to take up iodide in rat thyroid cells (27,37).The transport of iodide is a fundamental step in thyroid hormone biosynthesis and is catalyzed by the Na ϩ -I Ϫ symporter (NIS), an intrinsic membrane protein localized at the basolateral membrane of thyrocytes (20). Leptin directly inhibits iodide uptake induced by TSH in FRTL-5 cells (27) and in thyroids from fed adult rats (37).…”
mentioning
confidence: 95%
“…These observations indicate a direct stimulatory effect of leptin on the thyroid gland or on the peripheral metabolism of T 4 and T 3 in humans with reduced body weight. On the other hand, recent studies have shown direct inhibitory effects of leptin on the ability of thyrocytes to take up iodide in rat thyroid cells (27,37).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In rat thyroid FRTL-5 cells, leptin induced an increase in c-fos expression and TSHstimulated cAMP production (15). However, leptin inhibited iodide uptake induced by TSH as well as TSH-and cAMPinduced NIS and thyroglobulin expression.…”
Section: Discussionmentioning
confidence: 89%
“…Leptin stimulates thyrotropin-releasing hormone (TRH) expression in the hypothalamus, and subsequently production of thyroid-stimulating hormone (TSH). Peripherally, limited studies suggest that leptin has direct actions on the thyroid gland (15). It has been demonstrated that rats receiving prolonged leptin treatment had increased thyroid gland weight (16).…”
Section: Introductionmentioning
confidence: 99%